Effect of Bi2O3 on the optical and radiation shielding properties of borotellurite glasses irradiate at 59 keV photon energy - Alias, N.H.; Zaid, M.H.M.; Matori, K.A.; Fen, Y.W.; Nazrin, S.N.; Effendy, N. (Elsevier Ltd, 2025)
The optical and radiation shielding properties of the newly formulated bismuth borotellurite, [Bi2O3]x[(TeO2)70(B2O3)30]100-x glass system with x = 0, 5, 10, 15, and 20 mol% irradiated at 59 keV photon energy have been investigated. X-ray diffraction analysis confirm the amorphous structure of the glasses. The density of the glass sample increase from 3.962 to 6.400 g/cm3 with the increase of Bi2O3 concentration. From the results, the molar volume and oxygen packing density revealing an anomaly trend for the sample at a concentration 10 mol% of Bi2O3. Besides, the FTIR spectra showed an increase in the formation of bridging oxygen (BO) species, specifically BO4 bond as the progress of Bi2O3 concentration. According to the optical results, the optical band gaps decreased from 2.53 to 1.75 eV, the refractive index increase from 2.54 to 2.85, molar refraction increase from 21.56 to 23.32 cm3/mol and metallization decrease from 0.36 to 0.30 as the concentration of Bi2O3 increased within the glass matrix. This reduction in optical band gap is attributed to the rising basicity and polarizability. The addition of higher concentrations of Bi2O3 enhances the radiation shielding effectiveness of the glasses, as evidenced by the increased mass attenuation coefficient, ranging from 1.086 to 1.506 and half-value layer values. The lowest half-value layer is achieved for the glass sample 10 mol% Bi2O3 with the density of 4.968 g/cm³, measuring 0.096 cm at 59 keV photon energy. This indicates superior shielding resistance at low radiation energy, minimizing the thickness requirements of the radiation instrument in the medical field.